TAC METHOD TO OVERCOME THE PRACTICAL DIFFICULTY IN THE CALIBRATION OF DWT WITH INSENSITIVE PISTON - Adindra Vickar Ega; Rudi Anggoro Samodro (Instrumentasi, 2019)
The crossfloat (CF) method is well-known for its accurate and reliable results, however the difficulty on performing CF method arises when dealing with insensitive piston of calibrated DWT. In contrary, automatic transducer assisted crossfloat (TAC) method could be implemented since it does not affected by this condition as it advantages. The used of TAC method could avoid up to 0.008% relative error of effective area at zero pressure and at 20 °C (A0,20) and twice higher error distortion coefficient (b) in case of calibrating insensitive piston of DWT. In addition, the TAC method has another advantage that is save time with consistent result because it can be performed automatically. Once should be consider when using TAC method is the accuracy of pressure transducer. In this case study, the existing pressure transducer owned by RCM – LIPI, could be utilized to perform automatic TAC method in lower pressure range down to 2 MPa that below 10% of its maximum scale, to calibrate low accuracy DWT greater than 0.08%.